Case Report: Esthesioneuroblastoma Involving the Optic Pathways - da Silva, Vithor Ely B.; Buniatti, Samuel R.; Costa, Felipe D'Almeida; Torrecillas, Mauricio R.; de Oliveira, Jean G.; Rassi, Marcio S. (Frontiers in Surgery, 2022)
Olfactory neuroblastoma, or esthesioneuroblastoma, is an uncommon malignant tumor originating from the neural crest that commonly occur in the upper nasal cavity. Its ectopic origin is extremely rare, especially when located in the optical pathways. This paper reports the case of a giant ectopic esthesioneuroblastoma of the optic pathways that was surgically treated through a cranio-orbito-zygomatic craniotomy with extensive resection, in addition to a literature review. The patient is a 46-year-old female presenting with a 4-month history of visual loss in the left eye. Since she was previously blind in the right eye from a traumatic injury, it was evolving to loss of bilateral vision. Imaging depicted an expansive infiltrating lesion involving the entire path of the right optic nerve, extending to the optic chiasm, cisternal portion of the left optic nerve, bilateral optic tract, and hypothalamus. Investigation of pituitary function was unremarkable. Esthesioneuroblastoma is a rare tumor with poorly defined standard clinical management. Its ectopic presentation makes the diagnosis even more challenging, making it difficult to manage these cases properly. Surgeons should be aware of this rare possibility, as early aggressive treatment is likely to be associated with better results.